Liver Cirrhosis/Severe Fibrosis Is a Risk Factor for Anastomotic Leakage after Colorectal Surgery - Samuel Andreas Käser; Irina Hofmann; Niels Willi; Felix Stickel; Christoph Andreas Maurer (Gastroenterology Research and Practice)
Purpose. Liver cirrhosis associated with high perioperative morbidity/mortality. This retrospective study determines whether liver cirrhosis represents a risk factor for anastomotic leakage after colonic anastomosis or not. Methods. Based on a prospective database with all consecutive colorectal resections performed at the authors’ institution from 07/2002 to 07/2012 (n=2104) all colonic and rectal anastomoses were identified (n=1875). A temporary loop ileostomy was constructed in 257 cases (13.7%) either due to Mannheimer Peritonitis-Index > 29 or rectal anastomosis below 6 cm from the anal verge. More than one-third of the patients (n=691) had postoperative contrast enema, either at the occasion of another study or prior to closure of ileostomy. The presence of liver cirrhosis and the development of anastomotic leakage were assessed by chart review. Results. The overall anastomotic leakage rate was 2.7% (50/1875). In patients with cirrhosis/severe fibrosis, the anastomotic leakage rate was 12.5% (3/24), while it was only 2.5% (47/1851) in those without (p=0.024). The difference remained statistically significant after correction for confounding factors by multivariate analysis. Conclusion. Patients with liver cirrhosis/severe fibrosis have an increased risk of leakage after colonic anastomosis.